2012
DOI: 10.1007/s10832-012-9735-2
|View full text |Cite
|
Sign up to set email alerts
|

Optical characteristics of Bi4-xEuxTi3O12 ferroelectric thin films on fused silica substrates

Abstract: Bi 4-x Eu x Ti 3 O 12 (BEuT) ferroelectric thin films were prepared on fused silica substrates by using chemical solution deposition technique. The attained samples had a polycrystalline bismuth-layered perovskite structure, and their optical properties were composition dependent. The thin film samples had good optical transmittance above 500 nm wavelength. A blue shift of the optical absorption edge was observed in the BEuT thin films with increasing Eu 3+ concentration. The optical band gaps of BEuT thin fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, perovskite oxides are an important class of dielectric materials, which have widely been used in microwave devices, smart sensors, and piezoelectric transducers. [8][9][10] Particularly, active ions doped barium strontium titanate has drawn great attention for its simultaneous ferroelectric and optical properties, 11,12 suggesting attractive applications in multifunctional optoelectronic devices. 3,13 Recently, our research group reported tunable and ultrabroadband NIR luminescence from Ni 2þ -doped ferroelectric perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, perovskite oxides are an important class of dielectric materials, which have widely been used in microwave devices, smart sensors, and piezoelectric transducers. [8][9][10] Particularly, active ions doped barium strontium titanate has drawn great attention for its simultaneous ferroelectric and optical properties, 11,12 suggesting attractive applications in multifunctional optoelectronic devices. 3,13 Recently, our research group reported tunable and ultrabroadband NIR luminescence from Ni 2þ -doped ferroelectric perovskites.…”
Section: Introductionmentioning
confidence: 99%